Effect of charcoal ash coconut shell from waste material at different size on the physical properties of bitumen - Abdullah, M.E. (Trans Tech Publications Ltd, 2017)
Environmental pollution caused by abundant wastes from agricultural activities has increased in recent years because of increased productivity. Agricultural waste recycling has been employed to solve this problem. Coconut shell charcoal (CSC) ash is a by-product of coconut shell (CS) used as a bitumen modifier to enhance the properties of the binder. This study investigated the effect of fineness charcoal ash from CS on the rheological properties of bitumen. Penetration, softening point, and viscosity tests were performed to determine the properties of the binder. Laboratory simulation of aging called rolling thin film oven test was applied in this study. CSC at different sizes (< 75μm, 75-150μm, and 150-300μm) was added to replace bitumen 60/70 PEN at 0, 10, 15, and 20 by weight of the binder, respectively. Result showed that the bitumen became more viscous and that the softening point of bitumen increased, whereas the rate of penetration decreased when CSC was incorporated. CSC at a proper amount improved the resistance of bitumen to temperature susceptibility. In addition, the modification of bitumen can relieve the effect of aging. Modified bitumen shows better result when incorporated with the finest particle (< 75μm) of CSC compared with other sizes. © 2017 Trans Tech Publications, Switzerland.